A new In2O3 and NiO co-loaded fly ash-based nanostructural geopolymer for photocatalytic H2 evolution. Issue 182 (24th July 2017) - Zhang, Yao Jun; Zhang, Ke; Kang, Le; Zhang, Li
ABSTRACT: A nanostructural alkali-activated fly ash-based geopolymer (AFAG) by co-loaded bimetallic oxide semiconductors of In2 O3 and NiO were firstly synthesized and used as an excellent nanocatalyst for production of hydrogen by water splitting. XRD results revealed that In2 O3 with average particle size of about 14 nm and NiO in the form of amorphous phase dispersed on the surface of AFAG support. UV-vis DRS and photoluminescence spectra showed that the 5In2 O3 -NiO/AFAG sample has the widest response to sunlight spectrum and the weakest photoluminescence spectrum, respectively. The 5In2 O3 -NiO/AFAG sample exhibits the excellent photocatalytic activity of H2 evolution of 3180 µmol/g under the irradiation of solar simulation source for 6 h due to its mesoporous structure coupled with In2 O3 and NiO.